Carcass wrote:
\(0<c<1\)
Quantity A |
Quantity B |
\(\frac{c-1}{c+1}\) |
\(\frac{1-c}{c-1 }\) |
Useful property: \(\frac{a-b}{b-a} = -1\)Here's why: we can take \(b - a\) and factor out \(-1\) to get: \(b - a = (-1)(-b + a)\)
Since \(-b + a = a - b\), we get: \(b - a = (-1)(-b + a)= (-1)(a -b)\)
So,\(\frac{a-b}{b-a} = \frac{a-b}{-1(a-b)}= -1\)
So our two quantities and now look like this:
QUANTITY A: \(\frac{c-1}{c+1}\)
QUANTITY B: \(-1\)
Since \(0<c<1\), we can be certain that \(c+1\) is POSITIVE
So, we can safely multiply both quantities by \(c+1\) to get:
QUANTITY A: \(c-1\)
QUANTITY B: \(-1(c+1)\)
Expand to get:
QUANTITY A: \(c-1\)
QUANTITY B: \(-c-1\)
Add \(1\) to both quantities:
QUANTITY A: \(c\)
QUANTITY B: \(-c\)
Add \(c\) to both quantities:
QUANTITY A: \(2c\)
QUANTITY B: \(0\)
Since we are told that \(c\) is positive,
Quantity A must be greaterAnswer: A